Gas migration prevention using hydroxypropylmethylcellulose as a multifunctional additive in oil well cement slurry - Abbas, G. (Society of Petroleum Engineers, 2013)
This paper introduces Hydroxypropylmethylcellulose (HPMC) polymer, first time ever as a multifunctional additive for oil well cementing applications. This work is demonstrated by laboratory experiments. In which, API properties of HPMC based cement slurries were determined. From these experimental results, HPMC polymer effectively controlled fluid loss of cement slurry up to the temperature of 190 .F. HPMC completely prevented free water and it has excellent rheology at ambient and high temperatures. In addition, HPMC was found to develop an impervious barrier for prevention of gas migration. Further it was quantified by cement hydration analyzer. It was confirmed that HPMC based cement slurry was gas-tight formation. Such as pore pressure was remained constant at 16 psi with continues injection of gas at 150 psi for 08 hours. In addition, thickening time was increased 3:23 to 5:54 hours by the addition of HPMC polymer in cement slurry. The gas migration prevention was also confirmed through transition time of cement slurry. That was obtained as less than 30 minutes, which is excellent for gas migration prevention according to API criteria. Meanwhile, compressive strength was improved at 0.20 to 0.40 gallon per sack of HPMC polymer in cement slurries at 190 .F. This study showed that HPMC performed as an effective multifunctional additive and overall decreasing the quantity of additives in cement slurry. HPMC polymer comprehensively improved the properties of cement slurry. Thus, it can be effectively used as gas migration preventer at high temperature in field applications. Â© 2013, Society of Petroleum Engineers.